China–US Tensions: Is Globalisation Dead?. Issue 2 (2nd April 2020) - Harris, Jerry
ABSTRACT: Although the trade war between China and the US has aspects of a national rivalry, at a deeper level it is a struggle over different forms of globalisation. The Chinese and US economies are deeply integrated, but the economic crisis of 2008 caused a delegitimisation of neoliberalism. The transnational capitalist class is seeking to build new hegemonic projects to stabilise global capitalism. On one side is militarised and repressive accumulation surrounded by a nationalist narrative as typified by the Trump administration; and on the other is green capitalism. An economic and political project in which China plays a key role.